Islam Dalam Globalisasi : Tantangan Agama Dalam Manajemen Keutuhan Umat - Kausar AS (Millah: Journal of Religious Studies, 2012)
Globalization on the one hand is a historical necessity that goes without defense, and on the other hand Islamic values should be maintained and continues to be an option in the structuring of a better life. Some answers can be studied more closely in order to manage the integrity of the people, which includes the development of the spirit of togetherness that make up a new collective solidarity, increasing maturity in dealing with the times, increased provision emancipative knowledge and awareness to build intelligent communications with all elements of society. With the provision of intelligent religious community, an integrative synergistic communication people are more likely to be built in order to ensure integrity. Choice of strategy leads to other forms of identity shared maintenance; preservation of religious institutions; return of the strategic position and function of religious leaders, and the return values systems and symbolic systems in accordance with the material and spiritual needs of people. Thus, communication is not just wake up based on the similarity of religion, but also with people of other faiths who have differences may not be united.